Adobe Photoshop 7.0 - Reding, Elizabeth Eisner (Cengage Learning, Inc, 2003)
Part of the Design Professional Series, this text includes full-coverage of basic through more advanced skills such as how to work with layers, use paint tools and create Photoshop images for the Web